A Rare Case of Twinning Involving Primary Maxillary Lateral Incisor with Review of Literature - Hunasgi, Santosh (J Clin Diagn Res, 2017)
Twinning is referred to the development of two separate teeth that arose from the complete separation of one tooth bud. To the best of our knowledge very few cases of twinning in primary or permanent dentition have been previously reported. Here, we report an additional case of twinning involving primary maxillary left lateral incisor and a literature review of clinical and radiographic findings of previous reported cases of gemination and twinning is also discussed. A six-year-old male patient reported to the dental clinic with the complaint of decay in the left front teeth region of the upper jaw. On clinical examination, dentinal caries was observed on the labial surface of primary maxillary left lateral incisor. The tooth showed a deep groove present in relation to the labial surface and incisal edge and continued cervically as a shallow groove. The patient had normal compliment of teeth for his age. The intra-oral periapical radiograph of the maxillary anterior region revealed large crown and a radiolucent notch was observed in relation to the incisal edge of the maxillary left primary lateral incisor. Relatively one pulp chamber and two root canals were observed in relation to the primary maxillary left lateral incisor, which was suggestive of a case of twinning involving primary maxillary left lateral incisor. This present case is the first case report of twining seen in primary dentition.